TARI JEPIN KEMBANG MANGGAR DIKELURAHAN BATU LAYANG KECAMATAN PONTIANAK UTARA - Sumiati, Sumiati; Ismunandar, Ismunandar; Istiandini, Winda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe Jepin Kembang Manggar dance that has never been shown in the Batu Layang village of Pontianak Utara District has been the concern in this Study. This study was aimed at revitalizing the Jepin Kembang Manggar dance in Batu Layang village, manifested in discussions about the form, process, and results of the revitalization. The descriptive method with the form of qualitative and choreography approach was used in this study. The results of the research were several efforts completed to revitalize the Jepin Kembang Manggar dance in order to preserve and develop it in the community, especially in Batu Layang village, Pontianak Utara district. Firstly, the researcher met the first and second informants, followed by a meeting with the head of the dance studio along with dancers and musicians from the local community. Then, the dancers did the practices 6 times, as well as the musicians, did the practices 5 times along with the dancers. The Jepin Kembang Manggar dance was performed on Saturday, 9th of February 2019 at 19.30, accompanied by the music and equipped with dance properties and costumes. Finally, this dance performance received a lot of appreciation and support from the community in order to revitalize one of the cultures in the Batu Layang village, Pontianak Utara District.Keywords: Revitalization, Jepin Kembang Manggar dance, Batu Layang Village